Error Analyses on Numerical Differentiation and Integration - PURNAMA (NIM 13104022), FANDI
In measurement, differentiation and integration process of vibration measurement signal are often done. Differentiation and integration process is done numerically so that the result of differentiation and integration of measurement signal have error with respect to the true value (theoretic). Besides, generally measurement system is affected by noise so that cause error on the result of differentiation and integration. Therefore, analyses of error due to numerical differentiation and integration process and noise effect on numerical differentiation and integration is presented in detail in this research. Generally, this research is divided into two steps. First step is error analyses due to numerical differentiation and integration process. Second step is analyses of noise effect on numerical differentiation and integration. Each steps produces an equation which can be used to determine the error value due to numerical differentiation and integration process and noise effect on numerical differentiation and integration. Furthermore, to verify the equations which have been derive are correct, the equations are validated with the simulation results. The simulation are performed using computer program which is constructed using MATLAB software. Based on the validation results, it can be concluded that the equations which have been derived are correct.